PENGARUH PEMBERIAN BERBAGAI DOSIS UREA PADA BEBERAPA VARIETAS SORGUM ( Sorghum bicolor L.) TERHADAP HASIL DAN MUTU BENIH - Ridha, Rifaatul; Zuhry, Elza; ', Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The research aims to determine the best dose of Urea to yield and seed quality in some varieties of sorghum. This research using a randomized block design consisting of two factors with 3 replications. The first factor was 4 varieties of sorghum those Kawali, Numbu, Pahat and Mandau and the second factor was 3 levels of Urea treatments (60, 120 and 180 kg Urea/ha). Parameter those observed were seed weight/m2, weight of 1000 seeds, first count test, standard germinator test, index value test and seedling growth rate. The mean separation of analysis of variance was tested using Duncan’s multiple range test at 5%. The result indicates that application of 60 kg Urea/ha gave the best result on Pahat and Kawali. Application of 120 kg Urea/ha and 180 kg Urea/ha on Pahat gave the best result compare to Kawali, Numbu and Mandau. Varieties Kawali and Mandau gives the best in seed quality on Urea treatments at a dosage of 120 kg Urea/ha.   Keywords : Sorghum, Urea, Seed quality